Karakterisasi Metil Ester Dari Minyak Biji Bunga Matahari dan Minyak Zaitun di Bawah Katalis KOH - Aman Santoso; Muhammad Roy Asrori; Sumari Sumari; Andyka Medarda Pradana (Journal of Engineering Science and Technology, 2023)
Fatty acid methyl esters can be obtained from the synthesis of vegetable oil with methanol using a base catalyst. Vegetable oil has potential as biodiesel feedstock, the methyl ester character of various vegetable oils is different, for example from sunflower seed oil and olive oil. The synthesis of methyl esters by conventional transesterification reactions generally takes 1-2 hours. The purpose of this study was to synthesize methyl esters from sunflower seed oil and olive oil with a KOH catalyst and to determine the yield and its characteristics. This research is a type of laboratory experimental research. The research was carried out in 3 stages which included (1) determination of the free fatty acid content (ALB) of the oil, (2) transesterification of the oil with methanol and potassium hydroxide as a catalyst, and (3) characterization of the synthesized methyl ester which included density, viscosity, and number. acid. The results showed that the yield of methyl esters synthesized by transesterification reaction of sunflower seed oil was 95.61% and the yield of methyl esters synthesized by transesterification reaction of olive oil was 95.09.%. The methyl ester characters synthesized from sunflower seed oil are, density of 0.906 g/mL, viscosity of 5.035 cSt, acid number of 1.21 g KOH/g. The methyl ester characters synthesized from olive oil by transesterification reaction are density of 0.909 g/mL, viscosity of 12.203 cSt, acid number of 0.629 g KOH/g.